Story-making as a method for business modelling. Issue 1 (19th June 2019) - Haggège, Meyer; Vernay, Anne-Lorène
Abstract : Purpose: Imagining a new business model is a creative process that requires entrepreneurs to define how a firm can create and capture value with a new activity. The literature emphasises various tools and approaches for prototyping business models. The purpose of this paper is to investigate the suitability of story-making as a means of designing new business models and to shed light on its potential for stimulating creative entrepreneurial thinking. Design/methodology/approach: This paper tests the use of story-making for business modelling in a real-life case to show its usefulness and shed light on its potential for stimulating creative entrepreneurial thinking. Findings: The authors argue that story-making should be recognised as an approach to business modelling that can foster creativity and empathy. Building on insights from design thinking literature, the paper shows that planning for a long exploratory phase is necessary to allow system thinking. It also shows that anchors can act as intermediary stopping rule and help manage complexity. Originality/value: The paper introduces an original method for crafting business models during early stages of the innovation process and argues that this method could also be used to design business processes, especially when they are not already formalised.